Orientasi Digital Marketing Pada Usaha Waralaba Di Kota Padang - Neswardi , Sepri; Wirda, Fisla; Afifah, Afifah; Chandra, Alhapen Ruslin; Afriyeni , Endang; Yuanita , Ika; Fitri , Sheiska Sebrina (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Franchising has become a popular business model in Indonesia, including in Padang City. Franchising offers entrepreneurs the convenience of starting a business with lower risks compared to building a business from scratch. This study aims to analyze the digital marketing orientation of local franchises operating in Padang city. The research method uses a quantitative approach that uses a questionnaire as the primary data source. The research population is Local Franchise Businesses in Padang city with a sample size of 96 franchise business managers. Purposive sampling technique. The data analysis technique is descriptive statistics. The findings provide an explanation of the three aspects of digital marketing orientation that can be drawn three things that need special attention from local franchise entrepreneurs in Padang City, namely the importance of informing all employees that digitalization in marketing activities is important for business progress. This makes all employees have the same interest and have the same responsibility in implementing it, digital marketing performance requires clear indicators, because with clear indicators it can be a reference material for the success of ongoing performance and regular meetings are needed to discuss business digital marketing planning, which can also be a place to evaluate what has been done.